Are there features in the skiing technique of elite cross-country skiers that change systematically with FIS-Point ranking? - Gløersen, Ø.; Myklebust, H.; Hallén, J.; Federolf, P. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
"Technique" is often considered a key factor for the success of an athlete. However, technique is difficult to quantify, difficult to compare between athletes, and it is difficult to identify what a "good" technique might be. The current study applied a principal component analysis (PCA) to quantify elite skiers` skating techniques and compared features of the movement with the sprint FIS-point ranking (www.fis-ski.com) of the athletes. It was hypothesized that specific features of the motion might characterize better skiers and might therefore correlate with their sprint FIS-point ranking.